FLEXIBLE ULTRASOUND COUPLING SYSTEM - MURDOCK, DAVID M (1979)
Essentially nonreflective coupling for ultrasonic waves is provided between a fluid medium confined in a rigid container and a biological specimen, such as a human body, through a container closing bellows system which incorporates a thin, flexible closing membrane that contacts and conforms to the contours of the specimen. A supportive bellows system between rigid parts of the fluid container and the membrane gives the membrane the essential properties of conforming to the contours of a specimen having variations in curvature (concavities and convexities) while having the ability to contain the fluid medium without rupture or undue distension when it is not supported externally, as by contact with the specimen. The supportive bellows system utilizes a pair of flexible toroidal members, one tubular and one U-shaped in cross section, attached to one another in series and having internal venting so that pressure within the toroids is governed by the pressure of the fluid inside the coupling bellows system. The container closing bellow system is fluid filled, the flexible closing membrane is tautly stretched over the tubular toroid member so that it is supported by the bellows system and forms a fluid-tight closure, and a vent means is provided to adjust pressure inside the said container closing bellows system.